1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Help With Half Reaction/Redox Equation

  1. Oct 28, 2005 #1
    Can anyone help me with this? I have my entire homework section done except for this. For some reason, even on the previous test, I cannot figure out how to do these.
    Here is the question. I hope I get this right, I haven't used LaTeX on this site much.:confused:

    Balance the following oxidation-reduction reactions by the half-reaction method.

    Ok, the LaTeX keeps saying reload page, I have been trying for the last 15 minutes and I can't get it to show up. So, I'll try it without.:tongue2:

    FeI3(aq) + Mg(s) ---> Fe(s) + MgI2(aq)

    Be sure to indicate the spectator ions, the oxidation reaction, the reduction reaction, the reducing agent, the oxidizing agent.

    Here is what I have so far:

    Half reactions:
    Fe^3+(aq) ---> Fe(s) + 3e- = Oxidizing Reaction/Reducing Agent.
    2e- + Mg(s) ---> Mg(aq) = Reducing Reaction/Oxidizing Agent.

    Balanced equation:
    2FeI3(aq) + 3Mg(s) ---> 2Fe(s) + 3MgI2(aq)

    I have the spectator ion as Iodine.

    I am pretty sure most of this is wrong, as I have no clue how to do these. If someone could help me out/point me in the right direction, I would appreciate it.
    If you have any questions about it, or need more info, let me know.
    Last edited: Oct 29, 2005
  2. jcsd
  3. Oct 29, 2005 #2
    scince FeI3 and MgI2 are in an aqueous solution they split like this Fe^+3 + I^-1 and Mg^+2 + I^-1 the I^-1 are the spectator ions so they cancle out
    your left with Fe^+3(aq) + Mg(s) ===> Fe(s) + Mg^+2(aq), the half reactions are as follows

    Fe^+3(aq) + 3e- ===> Fe(s)/reducing half reaction therefore Fe^+3(aq) is the oxidizing agent

    Mg(s) ===> Mg^+2(aq) + 2e-/oxidizing half reaction therefore Mg(s) is the reducing agent

    the electrons gained must = electrons lost, so we multiply the half reactions by the lcd of the electrons/lost/gained before combining them

    2*(Fe^+3(aq) + 3e- ===> Fe(s))
    3*(Mg(s) ===> Mg^+2(aq) + 2e-)
    2Fe^+3(aq) + 6e- ===> 2Fe(s)
    3Mg(s) ===> 3Mg^+2(aq) + 6e-
    2Fe^+3(aq) + 3Mg(s) ===> 2Fe(s) + 3Mg^+2(aq)
    to check we have the same net-charge(+6) and elements on both sides of the chemical equation
    Last edited by a moderator: Oct 29, 2005
  4. Oct 29, 2005 #3
    Looks like I almost had it. By almost had it I mean not even close.:rofl:

    Thanks for the help.:biggrin:
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook